St. Mary's Augustinian Priory, Devenish Island, south west angle of tower, door jamb and arch - O'Donovan, Danielle (My University, 2008)
Doorway under tower, moulding comprises from intrados: hollow chamfer, hollow chamfer, hollow chamfer. The workmanship here is very fine and the stone has held its surface dressing. This door is almost identical in moulding and quality to the south west door of the nave in Holycross Abbey, Co. Tipperary. This, like the chancel door, suggests the involvement of Tipperary/Kilkenny masons.
Door
Keywords: Architecture, Gothic -- Ireland; Fermanagh (Northern Ireland); Architecture, Augustinian; Gothic doorways; Late Medieval; mouldings, hollow